Traditional Chinese medicine (Shenqinlong Qingfei Peiyuan) alleviate pulmonary infection in immunodeficient mice by suppressing HMGB1 and reversing macrophage polarization - Meijun Liu; Xiyuan Song; Xiaoli Chen; Pengfei Meng; Qian Yu; Liran Xu; Aiping Lyu; Kenneth CP Cheung (Phytomedicine Plus)
Background: Pulmonary infections are a significant concern for HIV/AIDS patients, and the role of macrophage polarization is critical in this context. Shenqinlong Qingfei Peiyuan Granules (QFPY) have been reported to alleviate symptoms of these infections. This study aims to explore the mechanisms through which QFPY reduces lung infections by regulating macrophage polarization. Methods: We developed an immunocompromised mouse model using Balb/c mice, simulating HIV infection by inoculating them with Friend Leukemia Virus (FLV, VR-245). Pulmonary infection was induced by nasal administration of Streptococcus pneumoniae Type III (ATCC 49619). The mice received QFPY treatment for 14 days. Post-treatment, we collected thymus, spleen, and lung tissue samples. T lymphocyte counts (CD3+, CD4+, and CD8+) were measured, and CD86 and CD163 expressions in bronchoalveolar lavage fluid (BALF) from lung tissue were assessed using flow cytometry. Cytokine levels, including IL-1β, TNF-α, TGF-β1, and IL-10, were evaluated using enzyme-linked immunosorbent assay (ELISA). Additionally, HMGB1 mRNA and protein levels were measured using quantitative PCR (qPCR) and Western blot techniques. Results: QFPY treatment showed efficacy comparable to the current standard treatment for lung infections, levofloxacin tablets (LEV). In our immunocompromised mouse model, QFPY treatment reversed thymus shrinkage, reduced spleen swelling, increased T cell counts, and inhibited M1 macrophage polarization. These effects were achieved by suppressing the expression of HMGB1. Conclusions: QFPY effectively restored immune homeostasis and reduced inflammation in HIV/AIDS-related pulmonary infections by modulating HMGB1 expression.